Effects of errors in basal area and mean diameter on the optimality of forest management prescriptions - Ruotsalainen, Roope; Pukkala, Timo; Kangas, Annika; Packalen, Petteri (EDP sciences, 2021)
Errors in forest stand attributes can lead to sub-optimal management prescriptions concerning the set management objectives. When the objective is net present value, errors in mean diameter result in greater losses than similar errors in basal area, and underestimation greater losses than overestimation.
Keywords: Forest management planning; Inoptimality loss; Inventory error; Net present value; Value of information